2017
DOI: 10.3389/fnana.2017.00119
|View full text |Cite
|
Sign up to set email alerts
|

The Superior Fronto-Occipital Fasciculus in the Human Brain Revealed by Diffusion Spectrum Imaging Tractography: An Anatomical Reality or a Methodological Artifact?

Abstract: The existence of the superior fronto-occipital fasciculus (SFOF) in the human brain remains controversial. The aim of the present study was to clarify the existence, course, and terminations of the SFOF. High angular diffusion spectrum imaging (DSI) analysis was performed on six healthy adults and on a template of 842 subjects from the Human Connectome Project. To verify tractography results, we performed fiber microdissections of four post-mortem human brains. Based on DSI tractography, we reconstructed the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
2
21
0
1
Order By: Relevance
“…Tractography algorithms can lead to false connections or premature terminations of tracked fibers and thus be responsible for an anatomical inaccuracy between MRI-derived reconstruction and dissection (43). Similarly to our findings regarding the inferior fronto-occipital fasciculus, reconstruction of tracts that could not be identified on gross anatomical dissection has already been reported for the feline inferior fronto-occipital fasciculus (24,25,27,35) and the human superior fronto-occipital fasciculus (44,45). For this latter fasciculus, modeling errors are assumed to have generated false continuations between different projection fibers, thus leading to the reconstruction of a continuous fronto-occipital fiber bundle (45).…”
Section: Discussionsupporting
confidence: 83%
“…Tractography algorithms can lead to false connections or premature terminations of tracked fibers and thus be responsible for an anatomical inaccuracy between MRI-derived reconstruction and dissection (43). Similarly to our findings regarding the inferior fronto-occipital fasciculus, reconstruction of tracts that could not be identified on gross anatomical dissection has already been reported for the feline inferior fronto-occipital fasciculus (24,25,27,35) and the human superior fronto-occipital fasciculus (44,45). For this latter fasciculus, modeling errors are assumed to have generated false continuations between different projection fibers, thus leading to the reconstruction of a continuous fronto-occipital fiber bundle (45).…”
Section: Discussionsupporting
confidence: 83%
“…When tracts were compared between treatment resistant and responsive individuals, there were differences in regions of the corpus callosum and bilaterally in the fronto-occipital fasciculus [thought to be involved in semantic processing (Martino et al, 2010 )]. The findings in the fronto-occipital fasciculus should be interpreted with caution as the extent and connectivity of this tract is under debate (Bao et al, 2017 ). Other WM changes were observed in the left hemisphere only and located in the optic radiation, and the rostral segment of anterior limb of internal capsule.…”
Section: What Evidence Do We Have For Wm Changes In Schizophrenia Beimentioning
confidence: 99%
“…There has been a longstanding controversy regarding the existence of a superior occipito-frontal fasciculus in humans, whose putative stem would have been located, by analogy with the monkey anatomy, at the angle between the corpus callosum and the caudate nucleus, in close relationship with the cortico-striatal tract (also called the subcallosal fasciculus or Muratoff bundle; Schmahmann and Pandya, 2007 ). The putative SOF has never been evidenced by any dissection studies (Ture et al, 1997 ; Meola et al, 2015 ; Bao et al, 2017 ), but the controversy is still ongoing, and a recent tractographic study suggested that if such a tract existed, it would, rather, be a fronto-parietal one (Bao et al, 2017 ). In fact, it seems that such a bundle could be a remnant of a fetal pathway that could play a role in axonal guidance during a specific temporal window of brain development, explaining its involution in postnatal brain development and the difficulty in identifying this remnant in adult brains by dissection and tractographic studies (Vasung et al, 2011 ).…”
Section: Towards a Common Terminology For Long-range Association Fibementioning
confidence: 99%
“…Some previously described association pathways have also been more recently shown to potentially be methodological artifacts. For example, the superior fronto-occipital fasciculus is now considered to not exist in the human brain after having inherited several terminologies from animal studies, namely, the Muratoff or subcallosal fasciculus (Forkel et al, 2014 ; Meola et al, 2015 ; Bao et al, 2017 ). In the same vein, the initial name of a bundle has sometimes been generalized to describe an extension of the initial pathway, without a semantic relationship with the genuine pathway.…”
Section: Introductionmentioning
confidence: 99%